Transformation of lithium acetate-treated Neurospora with minipreps of plasmid DNA. - J. V. Paietta; G. A. Marzluf (Fungal Genetics Reports, 1984)
Transformation of lithium acetate-treated Neurospora with minipreps of plasmid DNA.